The role of marketing in education for sustainable consumption: A multiple case study of companies with sustainable positioning - Fiorenzo, Maria Fernanda Cury Camis Sisternas; Rocha, Thelma Valeria; Migliato, Caline (Journal of Sustainable Competitive Intelligence, 2025)
Purpose: to understand the role that marketing can play in educating consumers to acquire sustainable consumption habits. Methodology/approach: exploratory qualitative research based on the multiple case study method, with in-depth interviews with marketing managers and actions developed to educate the customers. Originality/Relevance: this study innovates by analyzing three cases of companies with sustainable positioning, verifying sustainable practices in their marketing mix as managerial contribution. Key findings: it was clear that they need to carry out an analysis of their value chains before applying sustainability elements to their marketing mix to educate their consumers. It is important that they first understand whether they are in fact acting sustainably, and then create actions in this direction. Theoretical/methodological contributions: the managerial model has shown that companies with a sustainable positioning can follow it to approach marketing strategies that educate their consumers in relation to sustainable consumption.